Forward electromagnetic scattering models for sea ice - Golden, Kenneth M.; Cheney, M., Ding, Kung-Hau, Fung, A. K., Grenfell, Thomas C., Isaacson, D., Kong, Jin Au, Nghiem, Son V., Sylvester, J., Winebrenner, D. P. (Institute of Electrical and Electronics Engineers (IEEE), 1998)
Journal Article Recent advances in forward modeling of the electromagnetic scattering properties of sea ice are presented. In particular, the principal results include the following: 1) approximate calculations of electromagnetic scattering from multilayer random media with rough interfaces, based on the distorted Born approximation and radiative transfer (RT) theory; 2) comprehensive theory of the effective complex permittivity of sea ice based on rigorous bounds in the quasi-static case and strong fluctuation theory in the weakly scattering regime; 3) rigorous analysis of the Helmholtz equation and its solutions for idealized sea ice models, which has led in the one dimensional (1-D) case to nonlinear generalizations of classical theorems in Fourier analysis.